2021
DOI: 10.1098/rspb.2020.2294
|View full text |Cite
|
Sign up to set email alerts
|

Psychoactive pollution suppresses individual differences in fish behaviour

Abstract: Environmental contamination by pharmaceuticals is global, substantially altering crucial behaviours in animals and impacting on their reproduction and survival. A key question is whether the consequences of these pollutants extend beyond mean behavioural changes, restraining differences in behaviour between individuals. In a controlled, two-year, multigenerational experiment with independent mesocosm populations, we exposed guppies ( Poecilia reticulata ) to environmentally realistic le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 72 publications
3
31
0
Order By: Relevance
“…Confirmation of our theory can be found in a recent Polverino et al. (2021) publication. The authors found strong evidence that fluoxetine impairs adaptive potential to environmental change in fishes.…”
Section: Discussionsupporting
confidence: 90%
“…Confirmation of our theory can be found in a recent Polverino et al. (2021) publication. The authors found strong evidence that fluoxetine impairs adaptive potential to environmental change in fishes.…”
Section: Discussionsupporting
confidence: 90%
“…The target molecule of fluoxetine (serotonin transporter, 5-HTT) is present in a wide variety of taxa [14], which gives fluoxetine the potential to affect non-target organisms. In fact, studies have shown that fluoxetine exposure can cause adverse effects in a range of aquatic organisms, including reduced fecundity in snails [15], impaired development in tadpoles [16] and disturbed behaviour in fish [1719]. Few studies, however, have examined the impacts on life-history traits at field-relevant concentrations, which is surprising considering that changes in these traits are expected to have dire fitness and evolutionary consequences [7,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Given that only a relatively small number of recent studies have examined how chemical stressors alter aspects of behavioural variation (e.g. Tüzün et al ., 2017; Polverino et al ., 2021), or how consistent individual differences affect behavioural responses to chemical stressors (Nanninga, Scott & Manica, 2020), the integration of behavioural ecotoxicology and consistent individual variation is clearly an important direction for future study (see Montiglio & Royauté, 2014).…”
Section: Addressing Ecological Complexitymentioning
confidence: 99%
“…Indeed, recent work embracing these innovations has revealed effects of pollutants on behavioural processes that were previously not possible to capture using conventional approaches. These range from neurotoxic insecticide‐induced migration delays in songbirds (Eng, Stutchbury & Morrissey, 2019) to the breakdown of behavioural diversity in fish populations exposed to pharmaceutical pollution (Polverino et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%